Using Benchmark Tests for Research State Memory Encoding in Finite State Machine - Zaichenko, O.; Zaichenko, N.; Galkin, P.; Tsekhmistro, R. (My University, 2021)
The synthesizer will automatically assign the state memory codes based on the most effective use of the target technology (e.g., binary, gray code, one-hot) in FPGA. But exists alternative, when user by himself choose type of memory encoding. There was considered user defined state coding method for Quartus Altera.
Keywords: FPGA; finite state machine; state memory; memory coding; synthesizer; one-hot; sequential; johnson; speed of performance